The promise and challenges of oral step-down therapy for infective endocarditis in South Africa – Rethinking endocarditis treatment - Engelbrecht, A; Pecoraro, AJK; Doubell, AF (SA Heart Journal, 2025)
Infective endocarditis (IE) remains a complex clinical challenge globally and in South Africa, where it predominantly affects a younger population. Historically, it was managed with prolonged intravenous (IV) antibiotic therapy, an approach mainly based on expert opinion and low-level evidence. However, recent studies, including the landmark Partial Oral Treatment of Endocarditis (POET) trial, have demonstrated that oral step-down therapy is a safe and effective alternative in selected, clinically stable patients. Modern oral antibiotics now exhibit pharmacokinetic profiles comparable to their IV counterparts, and multiple randomised controlled trials (RCT) have confirmed their efficacy in clearing bacteraemia. While oral step-down therapy has been adopted in high-income settings and incorporated into international guidelines, its implementation in South Africa faces significant challenges. These include a high burden of blood culture-negative infective endocarditis (BCNIE), unique pathogens, such as Bartonella species (spp.) and Mycobacterium tuberculosis (TB), systemic healthcare constraints, limited access to cardiac surgery, and barriers to patient education and followup. In South Africa, locally feasible strategies are required to enable the safe and effective use of oral step-down therapy. Continued local research is needed to guide policy and adapt global evidence to the realities of the South African healthcare system.